Film production management how to budget, organize, and successfully shoot your film - Cleve, Bastian (New York Routledge, 2018)
This new and updated fourth edition of Film Production Management provides a step-by-step guide on how to budget, organize, and successfully shoot a film and get it onto the big screen. Whether you are a film student or film production professional just getting started in the industry, this book is an indispensable resource for day-to-day business on the set.

Written by veteran filmmaker Bastian Cleve, this book will teach you how to:
-Break down a screenplay
-Organize a shooting schedule
-Create a realistic budget
-Find and secure locations
-Network with agents to find actors
-Hire a crew and communicate effectively with unions

The new edition features updated information on contracts, permits, and insurance; special tips for low-budget filmmaking; new information on digital workflows and production software; advice on green production practices; and expanded coverage of the role of the line producer.
Includes appendices (pages 185-206) and index (pages 207-214).
Purchased (Fastbooks : 22 April 2019); Selected by Prof. Amor Aljibe at 2019 College of Mass Communication Library Bookfair.
Keywords: Motion pictures -- Production and direction